Recommendations for the implementation of BRCA testing in ovarian cancer patients and their relatives. (August 2019) - Gori, Stefania; Barberis, Massimo; Bella, Maria Angela; Buttitta, Fiamma; Capoluongo, Ettore; Carrera, Paola; Colombo, Nicoletta; Cortesi, Laura; Genuardi, Maurizio; Gion, Massimo; Guarneri, Valentina; Incorvaia, Lorena; et al.
Graphical abstract: Abstract: The current availability of new Poly(ADP-ribose) Polymerase (PARP)-inhibitors for the treatment of ovarian cancer patients independently of the presence of a BRCA pathogenic variant, together with the validation of somatic test for the analysis of BRCA1/2 genes, involves the need to optimise the guidelines for BRCA testing. The AIOM-SIGU-SIBIOC-SIAPEC-IAP Italian Scientific Societies, in this position paper, recommend the implementation of BRCA testing with 2 main objectives: the first is the identification of ovarian cancer patients with higher probability of benefit from specific anticancer treatments (test for response to therapy); the second goal, through BRCA testing in the family members of ovarian cancer patients, is the identification of carriers of pathogenic variant, who have inheredited predisposition to cancer development (test for cancer risk). These individuals with increased risk of cancer, should be encouraged to participate in dedicated high-risk surveillance clinics and specific risk-reducing measures (primary and/or secondary prevention programs).